Ultraflexible and Lightweight Bamboo‐Derived Transparent Electrodes for Perovskite Solar Cells. Issue 33 (28th June 2019) - Zhu, Kaiping; Lu, Zheng; Cong, Shan; Cheng, Guanjian; Ma, Peipei; Lou, Yanhui; Ding, Jianning; Yuan, Ningyi; Rümmeli, Mark H.; Zou, Guifu
Abstract: Wearable devices are mainly based on plastic substrates, such as polyethylene terephthalate and polyethylene naphthalate, which causes environmental pollution after use due to the long decomposition periods. This work reports on the fabrication of a biodegradable and biocompatible transparent conductive electrode derived from bamboo for flexible perovskite solar cells. The conductive bioelectrode exhibits extremely flexible and light‐weight properties. After bending 3000 times at a 4 mm curvature radius or even undergoing a crumpling test, it still shows excellent electrical performance and negligible decay. The performance of the bamboo‐based bioelectrode perovskite solar cell exhibits a record power conversion efficiency (PCE) of 11.68%, showing the highest efficiency among all reported biomass‐based perovskite solar cells. It is remarkable that this flexible device has a highly bendable mechanical stability, maintaining over 70% of its original PCE during 1000 bending cycles at a 4 mm curvature radius. This work paves the way for perovskite solar cells toward comfortable and environmentally friendly wearable devices. Abstract : Biodegradable and biocompatible transparent conductive electrodes are fabricated from bamboo for flexible perovskite solar cells. After extensive mechanical tests, including bending and crumpling tests, they still exhibit excellent electrical performance and negligible decay. The bamboo‐based bioelectrode perovskite solar cell shows a record power conversion efficiency of 11.68%, maintaining over 70% of initial power conversion efficiency after the bending tests.